Behaviour of four different B16 murine melanoma cell sublines: C57BL/6J skin. Issue 2 (9th February 2015) - Danciu, Corina; Oprean, Camelia; Coricovac, Dorina E.; Andreea, Cioca; Cimpean, Anca; Radeke, Heinfried; Soica, Codruta; Dehelean, Cristina
Summary Transplantable murine melanomas are well‐established models for the study of experimental cancer therapies. The aim of this study was to explore the behaviour of four different B16 murine melanoma cell sublines after inoculation into C57BL/6J mice; and, more specifically to analyse skin changes, with respect to two specific parameters: clinical (tumour volume, melanin amount, erythema) and histological (H & E, S100, VEGF expression). Both non‐invasive and invasive analysis showed that B164A5 is the most aggressive melanoma cell line for C57BL/6J's skin, followed by B16F10 and then by diminished aggressive growth pattern by the B16GMCSF and B16FLT3 cell lines.